PENDAPATAN PASIF DAN AKTIF USAHA BISNIS - Wili Yoga Atmaja; Patmawati Patmawati (Adiba Aisha Amira, 2024)
Income is one of the key elements in the survival of companies and individuals. In the context of companies, income is the main source to cover operational costs and increase business capacity, while in individual life, active income serves to meet basic needs, while passive income has the potential to support long-term financial freedom. Factors that affect income include job opportunities, skills, capital, and motivation, while the difference between active and passive income lies in the way it is obtained and the level of risk faced. Although active income is more stable in the short term, passive income offers long-term benefits through wealth accumulation that is less dependent on direct involvement. However, the main challenge in obtaining passive income is adequate initial investment to build assets that can generate recurring income. A good understanding of both is essential for individuals and companies to design effective and sustainable financial strategies.